Complex Effects of Cytochrome P450 Monooxygenase on Purple Membrane and Bacterioruberin Production in an Extremely Halophilic Archaeon: Genetic, Phenotypic, and Transcriptomic Analyses - Müller, Walter J.; Smit, Martha S.; van Heerden, Esta; Capes, Melinda D.; DasSarma, Shiladitya (Frontiers in Microbiology, 2018)
Halophilic Archaea are known to produce a diverse array of pigments for phototrophy and photoprotection. The aim of this paper was to determine the role of a Halobacterium gene encoding the predicted cytochrome P450 monooxygenase (CYP174A1) in pigment synthesis through a combined genetic, phenotypic, and transcriptomic approach. We report on the observed phenotype changes (increased bacterioruberin levels and the loss of purple membrane) between the H. salinarum R1 and its CYP174A1-deletion mutant. In addition, we report on the whole-genome DNA microarray analysis, which supports the phenotype of purple membrane loss. This work expands our understanding of the bop-gene regulon, and its relation to carotenoid biosynthesis, and sheds light in our broader understanding of the role (s) of CYP174A1 in archaeal pigment synthesis. To date, this is the first study in which the physiological role of any cytochrome P450 monooxygenase (CYP450) in extremely halophilic archaea has been reported.